(untitled) (Research, Society and Development, 2019)
The purpose of this essay is to address reflections regarding the mediations between education, society and development, in order to understand the hegemony of the formative processes that constitute as a paradigm, in which the component characteristics of an ideal and standard subject work in the social imaginary of subject educated - although it remains an ideal to be achieved in a notion of competence. The problematization of such a stigmatizing process will be enriched through the questions raised about the relations between education and society, based on critical theory. The research methodology of this work is inserted in a hermeneutics of the reading of authors who subsidize the analysis on the subject of the educated subject in modernity. It is also based on data collected at a higher education unit. The results indicate, from Adorno (1995, p. 211), that “[...] é extremamente limitada a possibilidade de mudar os pressupostos objetivos, isto é, sociais e políticos que geram tais acontecimentos, as tentativas de se contrapor à repetição de Auschwitz são impelidas necessariamente para o lado subjetivo”. We conclude that an instrumental focus prevails as an educational paradigm, which consists in a cold and calculated attitude, in which the idea of effectiveness and efficiency are valued triumphs as the notion of self pride for the individual to become an able and competent for entering the labor market, which, in turn, is based on a structure of hierarchy of subject subordination.